Mobile Access Safety : Beyond BYOD. - Assing, Dominique (ISTE., 2013)
Over the last few years, mobile equipment to remotely connect to the corporate network (smartphones, ultra-light laptops, etc.) has rapidly grown. Future development perspectives and new tendencies such as BYOD (Bring your own device) expose more than ever business information system to various compromising threats. The safety control of remote accesses has become a strategic stake for all companies. This book reviews all the threats weighing on these remote accesses, as well as the existing standard and specific countermeasures to protect companies, from both the technical and organizational.